1923
DOI: 10.1017/s002531540001095x
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphate Content of Fresh and Salt Waters in its Relationship to the growth of the Algal Plankton

Abstract: On account of the minute quantities in which they are present and of the fact that they are considered of secondary importance as indicating sewage contamination, phosphates are not usually estimated in analyses of natural waters. The tediousness of the determination also militated against it in the past. As a result, of the numerous analyses recorded by Clarke (1920), but few mention phosphates. C. H. Stone's analysis of the Mississippi in 1905, carried out upon a sample above Carrolton, Louisiana, shows 0.27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

1930
1930
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(44 citation statements)
references
References 8 publications
0
44
0
Order By: Relevance
“…In Plymouth, all effort then went into studying phosphate as the limiting factor. In a suite of field studies in the Channel it was shown that, just at the end of the spring bloom, not only had phosphate become depleted, but also that once the surface waters had warmed, the resulting vertical stratification prevented upward mixing of underlying phosphate-rich waters (ATKINS, 1923(ATKINS, , 1924(ATKINS, , 1925a. The concept of nutrient limitation by vertical stratification was consistent with earlier observation of the upper mixed layer in lakes, known as the epilimnion (BIRGE andJUDAY, 1911, 1922).…”
Section: Atkins Cooper and Harvey: Phosphate And Hydrographymentioning
confidence: 99%
“…In Plymouth, all effort then went into studying phosphate as the limiting factor. In a suite of field studies in the Channel it was shown that, just at the end of the spring bloom, not only had phosphate become depleted, but also that once the surface waters had warmed, the resulting vertical stratification prevented upward mixing of underlying phosphate-rich waters (ATKINS, 1923(ATKINS, , 1924(ATKINS, , 1925a. The concept of nutrient limitation by vertical stratification was consistent with earlier observation of the upper mixed layer in lakes, known as the epilimnion (BIRGE andJUDAY, 1911, 1922).…”
Section: Atkins Cooper and Harvey: Phosphate And Hydrographymentioning
confidence: 99%
“…Of the reagents so far suggested for the reduction of phosphomolybdic acid to molybdenum blue in the determination of phosphate, only stannous chloride (Atkins, 1923;Harvey, 1948), metol (Burton & Riley, 1956), and ascorbic acid (Greenfield & Kalber, 1954), give colours of sufficient intensity to be used in the analysis of sea water. Burton & Riley (1956) have recently reviewed the use of stannous chloride as a reducing agent in the molybdenum-blue method for the determination of phosphate in sea water.…”
mentioning
confidence: 99%
“…The diatoms in the rubidium-containing cultures seem to be limited to an increase of seven to eleven times their original number, so that even when the rubidium is not harmful the total replacement of potassium seems impossible. 4. It would seem that 3.1X 10-16gram atoms of potassium per diatom is approaching the limiting value of this element for the continued growth of Nitzschia closterium.…”
Section: Resultsmentioning
confidence: 97%
“…Atkins has shown (4) 1. It is fully realised that the difficulty in detecting potassium and rubidium when present in small quantities and together with salts of sodium, is very great.…”
Section: Resultsmentioning
confidence: 99%